2011
DOI: 10.1007/s00417-010-1586-4
|View full text |Cite
|
Sign up to set email alerts
|

“Seeing but not identifying”: pure alexia coincident with prosopagnosia in occipital arteriovenous malformation

Abstract: Ophthalmologists should keep in mind that usual complaints of "blurred vision" might correlate with unusual visual recognition disorders. Pure alexia and prosopagnosia have not been reported to occur together and the left-handed- dominance in our case leads to this scarce concurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…While a direct comparison is thus missing, one report shows that VWFA is involved in memorization of words and faces [Mei et al, ]. Moreover, there are case reports of prosopagnosic individuals with right fusiform lesions, which also show an impairment of their reading ability [Behrmann and Kimchi, ], as well as of individuals with left hemispheric lesions, which suffer from both, pure alexia and prosopagnosia [Liu et al, ]. Recently, functional imaging at higher resolution has shown that face‐sensitive sites on the fusiform gyrus are not arranged as one homogenously organized area but in several distributed cortical patches, which alternate with patches of different functional specialization [Weiner and Grill‐Spector, ].…”
Section: Discussionmentioning
confidence: 99%
“…While a direct comparison is thus missing, one report shows that VWFA is involved in memorization of words and faces [Mei et al, ]. Moreover, there are case reports of prosopagnosic individuals with right fusiform lesions, which also show an impairment of their reading ability [Behrmann and Kimchi, ], as well as of individuals with left hemispheric lesions, which suffer from both, pure alexia and prosopagnosia [Liu et al, ]. Recently, functional imaging at higher resolution has shown that face‐sensitive sites on the fusiform gyrus are not arranged as one homogenously organized area but in several distributed cortical patches, which alternate with patches of different functional specialization [Weiner and Grill‐Spector, ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were some overlaps of neural selectivity between faces and words in early perceptual processing [30]. Additionally, face recognition impairments were more severe following bilateral than unilateral lesions [31] and a left occipital arteriovenous malformation resulted in both pure alexia and prosopagnosia [32]. However, previous studies were designed to examine the sex differences of the N170 component for faces or words separately.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, alexia with agraphia points specifically to the posterior parietal lobe. It would not be wrong to mention that in pure alexia, a disconnection is present between the visual cortex and angular gyrus, so that visual-verbal unity is harmed (32). Marsh and Hillis (33) evidenced in a dependable manner with test batteries that such a linguistic deficit is not engendered by right hemineglect.…”
Section: Language Disorders and Thalamusmentioning
confidence: 99%